EDUKASI DAN PENANGANAN NYERI LUTUT SERTA MEMPERKENALKAN PELAYANAN FISIOTERAPI PADA MASYARAKAT DI DUSUN RECO DESA SITIREJO - Nurul Halimah; Eva Fatmawati; Lion Wahyu Dirgantara; Adisty Wintang Kartika; Adhe Firmansyah (CV Abid Abadi Jaya, 2025)
Knee osteoarthritis (OA) is one of the most common degenerative musculoskeletal disorders, significantly affecting the quality of life of older adults, particularly in rural areas with limited access to healthcare services such as Reco Hamlet, Sitirejo Village, Wagir District, Malang Regency. This community-based physiotherapy empowerment program was conducted by physiotherapy students during their community service project, aiming to improve awareness, prevention, and management of knee OA through a comprehensive community approach. The methods included field observation, postural screening, functional knee examination (range of motion/ROM, palpation, and Timed Up and Go Test), group education sessions, and simple physiotherapy interventions such as quadriceps strengthening (quad sets), bridging exercises, leg strengthening, ROM exercises, and conservative pain management using TENS